EFISIENSI PENGGUNAAN TEMPAT TIDUR MENGGUNAKAN GRAFIK BABER JOHNSON DI MASA PANDEMI COVID 19 - Astri Sri Wariyanti; Harjanti Harjanti (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2023)
The evaluation of bed use efficiency can be seen through the Barber Johnson Graph, where the graph contains efficient areas that can assess and present the efficiency of bed use and display four indicators of hospitalization, namely BOR, LOS, TOI, and BTO. In mid-2020, the number of TTs changed from 203 to 222, with an average number of 216 TTs. The purpose of the study was to determine the efficiency of using TT during the Covid-19 pandemic. The type of research is the mx method, the object of the Inpatient Daily Census Recapitulation. The BOR value is below the Ideal standard, the AvLOS is ideal, the TOI exceeds the Ideal value limit, the BTO is ideal. The efficiency of the use of TT is outside the efficient area because the number of patients decreases but the number of TT increases which causes a low BOR value with a high TOI. It is advisable to promote service facilities, allocate TT, establish health service standards, educate on Covid-19 service procedures.